Energianalys av hygieniseringssystem - Grim, Johanna (2014)
The biogas plant Kungsängens gård, owned by Uppsala Vatten och Avfall AB, produces biogas and biomanure from organic household waste, food processing waste and slaughterhouse waste. In year 2012, 4.4 million Nm3 of biogas were produced from 25 200 tons of waste. Before digestion all substrate is sanitized by one hour’s pasteurization at 70°C in order to kill pathogens. Another method, integrated thermophilic sanitation (ITS), is of interest in order to decrease the energy demand. The method implies that the substrate is sanitized during ten hours in the digestion chamber, where the temperature is 52°C.